Photography and the disruption of memory and meaning. Issue 1 (1st October 2014) - Fawns, Tim
By taking and sharing photographs, we are positioned within powerful communication networks that influence our personal and social identities. Over time, ownership and control is lost as our photographs gain performativity that allows them to divert from the purposes, spaces and times for which they are created. These issues are magnified by a number of technological, cultural and economic factors that accompany the evolution of ubiquitous digital media and their associated tools. Given the role that photographs play in the reconstruction of individual and collective memory and history, it is worth considering what is captured by the camera and what happens after the shutter closes.